New perspectives to study the biomass allocation and its relationship with the functioning of plants in neotropical ecosystems (2006)
How plants respond to variation in the availability of abiotic resources is a central research topic in physiological ecology. Several optimal partitioning models have suggested a functional balance in the biomass allocated to the shoot and root with the following prediction: "plants shift their allocation towards shoots if the carbon gain of the shoot is impaired by a low level of above-ground resources, such as light and CO2. Similarly, plants shift allocation towards roots at a low level of below-ground resources, such as nutrients and water". These shifts could be seen as adaptive, as they enable the plant to capture more of those resources that most strongly limit plant growth. Some methodological frameworks pretend to prove this prediction trough the description and analysis of biomass allocation, these are  discussing here. We emphasize that the conclusion in favor or against of this prediction is due to interpret in different ways the plasticity term. The last have induced to use methodologies which are suggesting that the prediction not be fulfilled in response to the availability of some resources. We propose the utilization of a research protocol to study biomass allocation patterns and suggest a methodology to quantify the plasticity of different genotypes from a discrete viewpoint.